Increased local failure for patients with intermediate‐risk rhabdomyosarcoma on ARST0531: A report from the Children's Oncology Group. Issue 18 (7th June 2019) - Casey, Dana L.; Chi, Yueh‐Yun; Donaldson, Sarah S.; Hawkins, Douglas S.; Tian, Jing; Arndt, Carola A.; Rodeberg, David A.; Routh, Jonathan C.; Lautz, Timothy B.; Gupta, Abha A.; Yock, Torunn I.; Wolden, Suzanne L.
Abstract : Background: The objective of this study was to evaluate local control for patients with intermediate‐risk rhabdomyosarcoma (RMS) treated on Children's Oncology Group (COG) protocol ARST0531. Methods: This study analyzed 424 patients with intermediate‐risk RMS. Patients were randomized to chemotherapy with either vincristine, dactinomycin, and cyclophosphamide (VAC) or VAC alternating with vincristine and irinotecan. With the goal of improving local control, radiation therapy (RT) was delivered early at week 4 and was concurrent with irinotecan in the experimental arm. Individualized local control plans for children 24 months old or younger were allowed. Local failure on ARST0531 was compared with local failure on the preceding COG intermediate‐risk study, D9803. Results: For patients with group I/II alveolar RMS (n = 55), the 5‐year cumulative incidence of local failure was 13.4%; for group III alveolar RMS (n = 141), it was 20.2%; and for group III embryonal RMS (n = 228), it was 27.9% ( P  = .03). Among patients with group III disease, local failure did not differ by histology, site, nodal status, RT modality, or treatment arm. Local failure was worse for a tumor size >5 cm (32.3% vs 16.7%; P  = .001). Among patients with group III embryonal RMS, local failure was higher on ARST0531 than D9803 (27.9% vs 19.4%; P  = .03). After the exclusion of patients 24 months old or younger or patients who did not receive radiation, local failure remained significantly increased on ARST0531 ( P  = .02). After adjustments for clinical prognostic factors, event‐free survival and overall survival were worse on ARST0531 ( P  = .004 and P  = .05, respectively). Conclusions: Despite interventions designed to enhance local control, local control was inferior on ARST0531 in comparison with D9803. The reason for this is unclear, but it could be the reduced cyclophosphamide dose on ARST0531. Abstract : One of the goals of the Children's Oncology Group protocol for patients with intermediate‐risk rhabdomyosarcoma (ARST0531) was to improve local control via the early introduction of radiation and the concurrent delivery of radiation with irinotecan, a known radiosensitizer. Despite these interventions, local control, event‐free survival, and overall survival are inferior on ARST0531 in comparison with the preceding Children's Oncology Group intermediate‐risk rhabdomyosarcoma study (D9803).